Electric-field-dependent photoconductivity in CdS nanowires and nanobelts : exciton ionization, Franz–Keldysh, and Stark effects - Li, Dehui (2013)
We report on the electric-field-dependent photoconductivity (PC) near the band-edge region of individual CdS nanowires and nanobelts. The quasi-periodic oscillations above the band edge in nanowires and nanobelts have been attributed to a Franz–Keldesh effect. The exciton peaks in PC spectra of the nanowires and thinner nanobelts show pronounced red-shifting due to the Stark effect as the electric field increases, while the exciton ionization is mainly facilitated by strong electron–longitudinal optical (LO) phonon coupling. However, the band-edge transition of thick nanobelts blue-shifts due to the field-enhanced exciton ionization, suggesting partial exciton ionization as the electron–LO phonon coupling is suppressed in the thicker belts. Large Stark shifts, up to 48 meV in the nanowire and 12 meV in the thinner nanobelts, have been achieved with a moderate electric field on the order of kV/cm, indicating a strong size and dimensionality implication due to confinement and surface depletion.